Mushrooms as a functional food mediator in Preventing and ameliorating diabetes Functional Foods in Health and Disease - Perera, P. K.; Li, Y. (My University, 2011)
From many reports it is clear that diabetes will be one of the major diseases in the coming years. As a result there is a rapidly increasing interest in searching new medicines, or even better searching prophylactic methods. Based on a large number of chemical and pharmacological research work, numerous bioactive compounds have been found in functional herbal food ingredients for diabetes. The present paper reviews functional herbal food ingredients with regards to their anti-diabetic active principles and pharmacological test results, which are commonly used in Asian culinary system and medical system and have demonstrated clinical or/and experimental anti-diabetic effectiveness. Our idea of reviewing this article is to give more attention to these functional food ingredients as targets medicinal foods in order to prevent or slow down the development of type 2 diabetes mellitus.